Determining quality indicators for projects of information protection of information activity objects - Lutsenko, Vladymyr; Progonov, Dmytro (Eastern-European Journal of Enterprise Technologies, 2023)
The design and analysis of the effectiveness of modern integrated information protection systems (IIPS) is complicated by the influence of the designer's subjective decisions regarding methods and means of protection, the need to determine the quality criteria for the functioning of the designed objects. The work is aimed at improving the technology of automated design of IIPS by determining the quality of projects. When creating a database (DB) of objects with such "qualitative" performance indicators of information protection systems, it is possible to compare existing and new protection objects and to adjust the protection projects of existing objects. Moreover, the ontological properties of active and threat-resistant objects are taken into account. To illustrate the use of the methodology for determining and comparing the quality of projects, an example of comparing the quality of projects obtained in different ways is given. One way currently operating involves the use of expert evaluation of the quality of protection projects for existing facilities. The second way is intended for objects defined as objects of protection of the general structure (OPGS) and involves a principally objective assessment of design quality using known quality diagrams and control of Ishikawa and Pareto design consequences. As a result of the given example, it was determined that the quality of projects according to quality diagrams and control of design consequences should increase by more than two times. The proposed method of comparing the quality of information protection projects for different objects or different protection projects of one object allows to improve the process of creating information protection projects. At the same time, it is possible to exclude the human controller from the process of determining the reliability of object protection. It also allows you to automate the design process, reduce the time and cost of design costs